Peroxidative damage of mitochondrial respiration is substrate-dependent - Endlicher, R; Křiváková, P; Rauchová, H; Nůsková, H; Červinková, Z; Drahota, Z (Physiological research, 2009)
The concentration-dependence of tert-butyl hydroperoxide (BHP) inhibitory effect on oxygen consumption in isolated rat liver mitochondria was measured in the presence of various respiratory substrates. Strong inhibitory effect at low concentrations of BHP (15-30 microM) was found for oxoglutarate and palmitoyl carnitine oxidation. Pyruvate and glutamate oxidation was inhibited at higher concentrations of BHP (100-200 microM). Succinate oxidation was not affected even at 3.3 mM BHP. Determination of mitochondrial membrane potential has shown that in the presence of NADH-dependent substrates the membrane potential was dissipated by BHP but was completely restored after addition of succinate. Our data thus indicate that beside peroxidative damage of complex I also various mitochondrial NADH-dependent dehydrogenases are inhibited, but to a different extent and with different kinetics. Our data also show that succinate could be an important nutritional substrate protecting hepatocytes during peroxidative damage.
Keywords: Male; spotřeba kyslíku; Rats, Wistar; membránový potenciál mitochondrií; Ketoglutaric Acids; Mitochondria, Liver; Oxidative Stress; Animals; potkani Wistar; Palmitoylcarnitine; buněčné dýchání; mužské pohlaví; tert-Butylhydroperoxide; Glutamic Acid; palmitoyl karnitin; krysa rodu Rattus; Oxygen Consumption; oxidační stres; kyselina jantarová; Rats; terc-butylhydroperoxid; kyselina pyrohroznová; zvířata; Pyruvic Acid; Cell Respiration; kyselina glutamová; jaterní mitochondrie; Membrane Potential, Mitochondrial; Succinic Acid; kyseliny ketoglutarové